Psychological functioning measures in patients with primary insomnia and sleep state misperception. (13th February 2013) - Dittoni, S.; Mazza, M.; Losurdo, A.; Testani, E.; Di, R.; Marano, G.; Di, M.; Farina, B.; Mariotti, P.; Mazza, S.; Della Marca, G.
<x xml:space="preserve">Abstract</x> Objective Sleep state misperception (SSM) is a term used in the International Classification of Sleep Disorders to indicate people who mistakenly perceive their sleep as wakefulness. SSM is a form of primary insomnia. The aim of this study was to record psychological functioning measures (anxiety, depression, ability to feel pleasure, obsessive–compulsive traits) in a population of patients with primary insomnia and to evaluate the relationship between these measures and the patients' perception of their sleep. Materials and Methods Seventy‐six consecutive patients with primary insomnia were enrolled: 34 men and 42 women, mean age 53.9 ± 13.1. Sleep study included the following: Pittsburgh Sleep Quality Index, Epworth Sleepiness Scale, Berlin's Questionnaire and home‐based polysomnography. Psychometric evaluation included the following: Self‐Administered Anxiety Scale, Beck's Depression Inventory, Maudsley's Obsessive Compulsive Inventory, Snaith–Hamilton Pleasure Scale, Eating Attitude Test. Results All patients with insomnia had psychometric scores higher than the general population, but very few patients, in both groups, had anxiety or depression scores consistent with severe mood or anxiety disorders. Comparisons between subjective and objective scores confirmed that most sleep parameters were underestimated. Patients with SSM had lower anxiety scores as compared to patients without SSM. Conclusions The study did not succeed in identifying any predictor of sleep misperception. We speculate that a group of patients, rather than being extremely worried by their insomnia, may have a sort of agnosia of their sleep.